2016
DOI: 10.20473/ijtid.v6i1.1207
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Justicia Gendarussa Burm F. Leaf Extracts on Molt-4 Cell

Abstract: Justicia gendarussa Burm f. (Acanthaceae) is known for its activity as a male contraceptive and anti-HIV properties. The present study was designed to evaluate extracts of J. gendarussa for cytotoxicity activity against MOLT-4 cells. The cytotoxic activity of the fractionated-extract and 70% ethanol extracts of J. gendarussa leaves on MOLT-4 cells were evaluated using a WST-1 assay. The treatment cells, control cells without treatment and control media were also tested in duplicate. The absorbance was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…The result showed an elimination half-life (t 1/2) of 243 in urinary excretion of 4.44±2.14 h, and the rate constant of elimination (Kel) was 0.18±0.07/h. 84) The 70% ethanol extract of these leaves is not toxic to MOLT-4 cells using a water-soluble tetrazolium-1 (WST-1) assay, with CC 50 values of 78 µg/mL. 85) The extract of this plant reduced cumulus oophorus dispersibility in vitro and testosterone concentration in mouse serum; therefore it may reduce mouse spermatozoa hyaluronidase.…”
Section: Justicia Gendarussamentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed an elimination half-life (t 1/2) of 243 in urinary excretion of 4.44±2.14 h, and the rate constant of elimination (Kel) was 0.18±0.07/h. 84) The 70% ethanol extract of these leaves is not toxic to MOLT-4 cells using a water-soluble tetrazolium-1 (WST-1) assay, with CC 50 values of 78 µg/mL. 85) The extract of this plant reduced cumulus oophorus dispersibility in vitro and testosterone concentration in mouse serum; therefore it may reduce mouse spermatozoa hyaluronidase.…”
Section: Justicia Gendarussamentioning
confidence: 99%
“…84) The 70% ethanol extract of these leaves is not toxic to MOLT-4 cells using a water-soluble tetrazolium-1 (WST-1) assay, with CC 50 values of 78 µg/mL. 85) The extract of this plant reduced cumulus oophorus dispersibility in vitro and testosterone concentration in mouse serum; therefore it may reduce mouse spermatozoa hyaluronidase. A pre-clinical study of an alkaloid free 70% ethanol extract of leaf extract has confirmed its male contraceptive activity.…”
Section: Justicia Gendarussamentioning
confidence: 99%
“…It is worth mentioning that there is currently relevant interest among research groups in evaluating a possible analgesic, anti-inflammatory and antiulcerogenic activity. A diversity of special metabolites is found in Justicia , mainly alkaloids [ 46 , 47 , 48 , 49 , 50 , 51 ], steroids [ 52 , 53 , 54 ], tannins [ 32 , 41 , 46 , 51 ], terpenoids [ 47 , 48 , 51 , 54 , 55 , 56 , 57 , 58 ], lignans [ 59 , 60 , 61 , 62 , 63 , 64 ] and flavonoids [ 16 , 20 , 21 , 22 , 23 , 24 , 31 , 32 , 51 , 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first part, namely releasing-alkaloid beetroot powder. The dried powder (820.0 g) was added with a weak citric acid solution to the formed water-soluble alkaloids salt (Widiyanti et al, 2016). Releasing-alkaloid beetroot powder was then extracted using hydroethanolic (ethanol: water, 70:30) for 3´24 h in a macerator.…”
Section: Preparation Of the Extractsmentioning
confidence: 99%